The Impact of Compensation, Work Environment, and Commitment towards Job Satisfaction on Private High School Teachers Performance in Makassar City - Rasmi Rasmi; Mahlia Muis; Maat Pono (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2020)
This paper aims to determine and analyze the impact of compensation, work environment, and organizational commitment towards job satisfaction on the performance of private high school teachers in the city of Makassar. The method used in this research is Descriptive Analysis method using path analysis regression. The population in this study were private high school teachers in the city of Makassar. The sample in this study was 88 teachers. Data collection using a questionnaire, while for testing the hypothesis using a simultaneous test and partial test and Path Analysis. The results of this study indicated that first, compensation has a positive and significant impact on job satisfaction. Second, the work environment has a positive and significant impact on job satisfaction. Third, organizational commitment has a positive and significant impact on job satisfaction. Fourth, compensation has a positive and significant impact on teacher performance. Fifth, the Work Environment has a positive and significant impact on teacher performance. Sixth, Organizational Commitment has a positive and significant impact on teacher performance. Seventh, Job Satisfaction has a positive and significant impact on teacher performance. Eighth, Compensation affects the performance of teachers who are mediated by job satisfaction. Ninth, Work Environment affects teacher performances that mediated by job satisfaction. And Tenth, Organizational Commitment influences teacher performance through job satisfaction.